2019
DOI: 10.1017/s0033291719003167
|View full text |Cite
|
Sign up to set email alerts
|

Suicide attempt and suicide in refugees in Sweden – a nationwide population-based cohort study

Abstract: Background Despite a reported high rate of mental disorders in refugees, scientific knowledge on their risk of suicide attempt and suicide is scarce. We aimed to investigate (1) the risk of suicide attempt and suicide in refugees in Sweden, according to their country of birth, compared with Swedish-born individuals and (2) to what extent time period effects, socio-demographics, labour market marginalisation (LMM) and morbidity explain these associations. Methods Three cohorts comprising … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
32
1
1

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 27 publications
(37 citation statements)
references
References 24 publications
3
32
1
1
Order By: Relevance
“…The number of individuals with acute suicidal tendencies in our sample was low. This is contrary to other studies that reported higher suicidality in refugees, including a population-based cohort [ 32 ] and compared to the general population [ 33 , 34 , 35 ]. However, as already stated before, the concept of suicidality may have lead to misunderstandings in our sample due to cultural differences.…”
Section: Discussioncontrasting
confidence: 99%
“…The number of individuals with acute suicidal tendencies in our sample was low. This is contrary to other studies that reported higher suicidality in refugees, including a population-based cohort [ 32 ] and compared to the general population [ 33 , 34 , 35 ]. However, as already stated before, the concept of suicidality may have lead to misunderstandings in our sample due to cultural differences.…”
Section: Discussioncontrasting
confidence: 99%
“…In general, refugees had a lower risk of both suicide attempt and suicide when compared to the Swedish-born population. Associations between refugee status and suicide attempt and suicide have rarely been investigated [8,9]. Hence, our study is one of the first to examine associations between mental disorders and suicide attempt and suicide in refugees.…”
Section: Key Resultsmentioning
confidence: 96%
“…Given these higher levels of psychiatric morbidity, it has further been hypothesized that refugees have an elevated risk of suicidal behavior, in terms of suicide attempt and suicide. However, there are hardly any studies examining this association [7][8][9]. One Danish study that investigated differences in injury mortality in refugees and immigrants reported lower rates of suicide [7] in refugees in comparison with the host Danish population.…”
Section: Introductionmentioning
confidence: 99%
“…In turn, these disorders are among the main risk factors for suicidal behaviour [4,5]. However, there is knowledge gap regarding whether risk of suicide attempt, compared with a country's host population, is different for refugees [6,7]. A recent cohort study in Sweden reported a lower risk of suicide attempt in refugees, compared with the Swedish-born population [7].…”
Section: Introductionmentioning
confidence: 99%
“…However, there is knowledge gap regarding whether risk of suicide attempt, compared with a country's host population, is different for refugees [6,7]. A recent cohort study in Sweden reported a lower risk of suicide attempt in refugees, compared with the Swedish-born population [7]. The knowledge gap in this field seems even more prominent in light of the increase in global migration in the recent decades.…”
Section: Introductionmentioning
confidence: 99%